Circulating biomarkers of one-carbon metabolism in relation to renal cell carcinoma incidence and survival. - Johansson, M; Fanidi, A; Muller, D; Bassett, J; Midttun, Ø; Vollset, SE; Travis, R; Palli, D; Mattiello, A; Sieri, S; Trichopoulou, A; Lagiou, P; et al. (2014)
BACKGROUND: The etiology of renal cell carcinoma (RCC) is only partially understood, but a metabolic component appears likely. We investigated biomarkers of one-carbon metabolism and RCC onset and survival. METHODS: The European Prospective Investigation into Cancer and Nutrition (EPIC) recruited 385747 participants with blood samples between 1992 and 2000, and this analysis included 556 RCC case-control pairs. A subsequent replication study included 144 case-control pairs nested within the Melbourne Collaborative Cohort Study (MCCS). Plasma concentrations of vitamin B2, vitamin B6, folate, vitamin B12, methionine and homocysteine were measured in prediagnostic samples and evaluated with respect to RCC risk using conditional and unconditional logistic regression models, and to all-cause mortality in RCC cases using Cox regression models. All statistical tests were two-sided. RESULTS: EPIC participants with higher plasma concentrations of vitamin B6 had lower risk of RCC, the odds ratio comparing the 4(th) and 1(st) quartiles (OR4vs1) being 0.40 95% confidence interval [CI] = 0.28 to 0.57, P trend < .001. We found similar results after adjusting for potential confounders (adjusted P trend < .001). In survival analysis, the hazard ratio for all-cause mortality in RCC cases when comparing the 4(th) and 1(st) quartiles (HR4vs1) of vitamin B6 was 0.57 (95% CI = 0.37 to 0.87, P trend < .001). Subsequent replication of these associations within the MCCS yielded very similar results for both RCC risk (OR4vs1 = 0.47, 95% CI = 0.23 to 0.99, P trend = .07) and all-cause mortality (HR4vs1 = 0.56, 95% CI = 0.27 to 1.17, P trend = .02). No association was evident for the other measured biomarkers. CONCLUSION: Study participants with higher circulating concentrations of vitamin B6 had lower risk of RCC and improved survival following diagnosis in two independent cohorts.